Towards Accurate and Certain Molecular Properties Prediction - Ham, Kyung Pyo; Yoon, Jeong Noh; Sael, Lee (International Conference on ICT Convergence, 2022)
In this review, we survey the fundamental problems and their solvers in molecular property prediction problems: graph neural networks modeling and uncertainty estimation. Molecules are naturally represented with graphs, thus graph neural networks, such as graph convolution networks and several types of message passing networks, are their natural models for accurate predictions. However, graph neural networks and any other deep learning models require a large amount of data. Unfortunately, molecular data are insufficient and skewed. Thus, not just an accurate method but models that return uncertainty estimations, such as Bayesian estimations, deep ensembles, and evidential methods, are required.
Keywords: AS graph; Graph neural networks; Model estimation; Molecular properties; Molecular property prediction; Network uncertainties; Neural network model; Prediction problem; Property predictions; Uncertainty estimation; graph neural network; molecular property prediction; uncertainty estimation